The Rising Challenge of Training Physician–Scientists: Recommendations From a Canadian National Consensus Conference. (February 2018) - Strong, Michael J.; Busing, Nick; Goosney, Danika L.; Harris, Ken A.; Horsley, Tanya; Kuzyk, Alexandra; Lingard, Lorelei; Norman, Wendy V.; Rosenblum, Norman D.; Saryeddine, Tina; Wang, Xin
Abstract : Physician–scientists are individuals who actively participate in patient care, have undergone additional research training, and devote the majority of their time to research. Physician–scientists are traditionally the primary catalysts in bridging the translational gap—that is, the failure to link fundamental new knowledge in the pathobiology of disease with advances in health care and health policy in a timely manner. However, there has been a shift away from training physician–scientists, and financial support for the physician–scientist is diminishing globally, causing the translational gap to grow. Given its socialized health care system and cultural and geographic diversity, Canada can serve as a unique case study in understanding how to address this phenomenon as a national priority. To this end, a Canadian national consensus conference was convened to develop recommendations for training programs and early-career supports for physician–scientists. Five recommendations were generated: (1) Establish an independent, national council whose mandate is to provide pan-Canadian oversight of physician–scientist training programs; (2) develop capacity for funding and mentorship support for physician-scientists; (3) develop coherent networks across a broad range of clinician–scientists, including physician–scientists, to reflect the unique cultural and geographic diversity of Canada and to reflect the interdisciplinarity of health research; (4) ensure that medical school curricula integrate, as a core curriculum feature, an understanding of the scientific basis of health care, including research methodologies; and (5) ensure that the funding of the physician–scientist trainee is viewed as portable and distinct from the operational funding provided to the training program itself.